Injury narratives in sport: a comprehensive review of qualitative studies - Weerasinghe, K.; Jayawardena, R.; Hills, A. P. (Psychology of Sport and Exercise, 2026)
This review aimed to systematically synthesize qualitative evidence on the perceptions, experiences, and practices of athletes and stakeholders regarding sports injuries, with a primary focus on risk factors, consequences, injury reporting, rehabilitation, and prevention strategies. A systematic review of qualitative studies was conducted in accordance with PRISMA guidelines and prospectively registered in PROSPERO. Six databases were searched from 2000 to July 2025. Eligible studies explored the lived experiences of sports injuries in athletes and stakeholders. Data were extracted, appraised using the CASP checklist, and synthesized thematically. Thirty-five studies were included, spanning a range of sports and competitive levels. Five overarching themes were identified: (i) risk factors including excessive training loads, poor recovery, early specialization, and psychosocial stressors; (ii) consequences of injury such as disrupted performance, long-term disability, financial costs, and significant psychological distress; (iii) rehabilitation highlighting both the challenges of self-management and the importance of interdisciplinary support; (iv) injury reporting and monitoring where normalization of pain, fear of deselection, and cultural pressures inhibited disclosure; and (v) injury prevention and performance sustainability emphasizing load management, evidence-based practices, collaborative monitoring, and contextual barriers such as limited resources and fixture congestion. Athletes and stakeholders perceive sports injuries as complex biopsychosocial phenomena shaped by cultural norms, resource availability, and interpersonal dynamics. Sustainable prevention requires both individualized and systemic approaches, combining tailored training plans, athlete-centered care, and structured surveillance systems. Qualitative insights highlight the necessity of embedding prevention and rehabilitation strategies within the lived realities of athletes, thereby enhancing health protection and long-term performance sustainability.